THE ASSOCIATION BETWEEN ASYMPTOMATIC BACTERIURIA AND GLYCEMIC CONTROL IN TYPE 2 DIABETES MELLITUS - Reni Marlina; Ricke Loesnihari; Santi Syafril (Indonesian Association of Clinical Pathologist and Medical laboratory, 2018)
The incidence of infection often occurs in patients with Diabetes Mellitus (DM) due to hyperglycemia that causes dysfunction of chemotaxis, phagocytic activity, malfunction of neutrophils and glycosuria. It is followed by other complications that lead to the malfunction of the bladder. Highly urinary glucose level is an exellent medium for pathogenic microorganisms growth. Asymptomatic Bacteriuria (ASB) is a risk factor for symptomatic urinary tract infection spontaneously or due to urinary catheters. This study aimed to analyze the association between the incidence of ASB of type 2 DM and glycemic control. The study was conducted during June-August 2016 with a cross-sectional method. Subjects were type 2 DM patients with age ≤60 years, who were treated in the Endocrinology Out-Patient Clinic of the Adam Malik Hospital. HbA1c was measured by Indiko automatic analyzer. Its association with urine culture results was analyzed. A total of 50 samples were enrolled, consisting of 25 females, and 25 males, with 19 having an exellent glycemic control (HbA1c <7%) and 31 with poor glycemic control (HbA1c ≥7%). Thirteen positive ASB were found, 5 with good glycemic control and 8 with poor glycemic control. Statistical analysis revealed a nonsignificant association between glycemic control and culture results (p = 1.000). Somers’d did not show a significant association between glycemic control and the incidence of ASB (p=0.968, d=-0.005). However, significant differences in culture results between gender, in which the ASB were found in samples of four females and two males (p=0.004). Somers’d revealed a significant association between culture results and gender (p=0.001; d=-0.360). Most of the bacteria found were Gram-negative. There was no significant association between glycemic control with an incidence of ASB. However, gender had significant differences in the incidence of ASB, which occurred more frequently in DM females than males. Urinalysis should be performed in patients with type 2 DM with ASB. However, further study was needed to analyze the relationship between glycemic control with the incidence of ASB and other factors that might affect the incidence of ASB.